Perlindungan Hukum Bagi Korban Penyalahgunaan Narkotika Usia Pelajar Di Wilayah Hukum Polres Malang - Syafiudin, Ahmad Taufik; Satindra, Gers Daviar (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2023)
Narcotics and Psychotropic are humanity crimes which in recent years have shown a fairly high trend of increasing. This problem certainly causes many victims, especially among the younger generation at the age of learning. In Indonesia, legal regulations regarding acts of drug abuse are regulated in Law no. 35 of 2009 concerning Narcotics. Based on these regulations, sanctions given for acts can be in the form of criminal sanctions and imposition of rehabilitation sanctions. This study aims to analyze the application of legal protection for victims narcotics victim abuse, as well as to analyze implementing legal protection for victims of narcotics abuse committed by students in the Malang Police jurisdiction. This research is empirical juridical research using a socio-cultural juridical approach, to examine the effectiveness of legal protection for victims of narcotics abuse in the jurisdiction of the Malang Police. The results of the study show that in addition to enforcing the law, legal protection is also implemented through rehabilitation for victims of narcotics abuse by students in the jurisdiction of the Malang Police. In an effort to implement it, investigators refer to the provisions contained in Law no. 35 of 2009 concerning Narcotics, and Permenkes No. 50 of 2015 concerning technical guidelines for the Implementation of Compulsory Reporting and Medical Rehabilitation for Addicts, Abusers, and Victims of Narcotics Abuse. The obstacles in implementing committed by students in the jurisdiction in the Malang Police, namely the difficulty of obtaining truth facts from victims or the dishonesty of narcotics abusers at student age which is influenced by fear and dependency, both in terms of economic, social, as well as emotional. In addition, there are also limited facilities and infrastructure for medical rehabilitation of narcotics abusers, as well as a lack of medical personnel who handle the rehabilitation of narcotics abusers in the Legal Area of ​​the Malang Police.